STRATEGI PENGEMBANGAN UMKM MELALUI PENGUATAN PEMASARAN DIGITAL DAN BRANDING PRODUK UNTUK MENINGKATKAN DAYA SAING USAHA - Maskanah; Ahmad Tarmizi; M Adkha Rosadi; Yanto Supono; Tahrudin; Koharudin; Fitri Rachmiati Sunarya (Haga : Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in promoting regional economic growth, creating employment opportunities, and improving community welfare. However, many business owners continue to face challenges in digital marketing, product identity development, business management, and market expansion, limiting their competitiveness. This community service program aimed to enhance the capacity of MSME owners through training and mentoring on digital marketing, product branding, business innovation, and business management across three partner MSMEs. The program employed a participatory approach consisting of needs assessment, interactive training, implementation mentoring, hands-on practice, and program evaluation. Participants actively engaged in developing digital promotional media, strengthening product identity, utilizing social media, and improving business management practices. The results demonstrated improved participants' understanding of digital marketing strategies, enhanced ability to utilize digital platforms for promotion, greater awareness of the importance of product branding, and strengthened capacity to manage their businesses in a more systematic manner. The program also encouraged MSMEs to adopt more structured promotional strategies, enabling them to expand market reach and improve business competitiveness sustainably.